2019
DOI: 10.1177/2516043519847330
|View full text |Cite
|
Sign up to set email alerts
|

Responding to health information technology reported safety events: Insights from patient safety event reports

Abstract: Objective: We analyzed the described resolutions of patient safety event reports related to health information technology to determine how healthcare systems responded to these events, recognizing that certain types of solutions such as training and education have a limited impact. Methods: A large database of over 1.7 million patient safety event reports was filtered to include those identified by the reporter as being related to health information technology. The resolution text was manually reviewed and cod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…First, previous research has highlighted the limitations of self-reported data that are applicable to the voluntary PSE reports studied in this analysis. 23 Secondly, since the PSE reports included in this analysis were derived from a single reporting system for hospitals based in the Mid-Atlantic region of the United States, our findings may not be generalizable across different geographic contexts. The nearly 82,000 PSE reports included in this analysis were, however, derived from hospital sites that did vary in other important ways such as teaching status, size, and whether sites served both urban and suburban patient populations.…”
Section: Discussionmentioning
confidence: 95%
“…First, previous research has highlighted the limitations of self-reported data that are applicable to the voluntary PSE reports studied in this analysis. 23 Secondly, since the PSE reports included in this analysis were derived from a single reporting system for hospitals based in the Mid-Atlantic region of the United States, our findings may not be generalizable across different geographic contexts. The nearly 82,000 PSE reports included in this analysis were, however, derived from hospital sites that did vary in other important ways such as teaching status, size, and whether sites served both urban and suburban patient populations.…”
Section: Discussionmentioning
confidence: 95%
“…Another area of concern related to patient safety is health information technology (IT). Researchers from MedStar Health's National Center for Human Factors in Healthcare and Georgetown University's School of Medicine recently analyzed 1.7 million patient safety events involving health IT . The researchers categorized responses according to one of four groups: no resolution, training and education, policy, and IT‐oriented solutions.…”
mentioning
confidence: 99%
“…14 Adams et al analyzed a large database to investigate how healthcare systems handled patient safety events related to Health Information Technology. 15 They found that nearly two-thirds of events had not been resolved at the time of reporting. Perhaps more important, they noted that the majority of the recommendations were for training and education of providers, types of solutions known to have limited impact.…”
mentioning
confidence: 99%